2011
DOI: 10.1088/0264-9381/28/21/215022
|View full text |Cite
|
Sign up to set email alerts
|

Holomorphic simplicity constraints for 4D spinfoam models

Abstract: Within the framework of spinfoam models, we revisit the simplicity constraints reducing topological BF theory to 4d Riemannian gravity. We use the reformulation of SU(2) intertwiners and spin networks in terms of spinors, which has come out from both the recently developed U(N ) framework for SU(2) intertwiners and the twisted geometry approach to spin networks and spinfoam boundary states. Using these tools, we are able to perform a holomorphic/anti-holomorphic splitting of the simplicity constraints and defi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
187
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(192 citation statements)
references
References 51 publications
5
187
0
Order By: Relevance
“…A recent review, containing a detailed discussion of the construction of some models can be found in [17,18]; other constructions are in [55][56][57][58][59][60].…”
Section: Simplicity Constraintsmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent review, containing a detailed discussion of the construction of some models can be found in [17,18]; other constructions are in [55][56][57][58][59][60].…”
Section: Simplicity Constraintsmentioning
confidence: 99%
“…The choice of the precise form of the constraint operator (which can be given in terms of so-called fusion coefficients) distinguishes the specific features encoded by the model at hand [55][56][57][58][59][60]. Furthermore, for fixed form of the operator S, we still have the freedom to decide where to apply it in the action: only in the kinetic term, only in the interaction term, or in both.…”
Section: Jhep06(2014)013mentioning
confidence: 99%
See 3 more Smart Citations